Transformational leadership and its role in driving organizational performance in the digital era - Ni Luh Eka Armoni; Ni Ketut Narti; Kadek Eni Marhaeni; Ni Luh Made Wijayati (YAYASAN MITRA PERSADA NUSANTARA, 2026)
In the contemporary digital era, organizations face unprecedented challenges and opportunities that require adaptive, visionary, and innovative leadership. Transformational leadership has emerged as a critical framework for guiding organizational performance through rapid technological change, market volatility, and evolving employee expectations. This article examines the role of transformational leadership in enhancing organizational performance by fostering innovation, digital readiness, and employee engagement. Drawing upon existing theoretical perspectives and recent empirical findings, the study highlights how transformational leaders inspire commitment, empower teams, and promote a culture of continuous learning that aligns with digital transformation strategies. The discussion further explores how digital tools and platforms provide new avenues for leaders to communicate vision, encourage collaboration, and drive organizational agility. Additionally, the paper identifies potential barriers to effective transformational leadership in the digital context, including resistance to change, skill gaps, and technological disruptions. By integrating leadership theory with contemporary digital practices, this article offers valuable insights for both scholars and practitioners in business management. The findings suggest that transformational leadership is not only essential for sustaining competitiveness but also for ensuring long-term organizational resilience in a rapidly changing environment.